2001
DOI: 10.1515/mgmc.2001.24.4.217
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Tetraaza Macrocyclic Complexes of Divalent Tin: Synthesis, Characterization and Fungicidal Properties

Abstract: Tin(II) complexes of tetraaza macrocycles have been prepared by template process using malonic, succinic and adipic acids with 1,2-diaminoethane and 1,3-diaminopropane. The reaction proceed smoothly to completion. The complexes were characterized by elemental analyses, molecular weight determinations, infrared and 'H NMR spectral studies. The elemental analyses are consistent with the formulation of complexes as [Sn(MacroC n )Cl 2 ]. All the complexes are stable and monomeric as indicate by molecular weight de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Due to the complexity of biological system, it is rather difficult to stipulate the exact mechanism for such activities. However, the increased biocidal properties after complexation can be very well explained by chelation theory [11]. Chelation reduces the polarity of the metal ion, mainly by the partial sharing of its positive charge with the chelate rings.…”
Section: Antimicrobial Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the complexity of biological system, it is rather difficult to stipulate the exact mechanism for such activities. However, the increased biocidal properties after complexation can be very well explained by chelation theory [11]. Chelation reduces the polarity of the metal ion, mainly by the partial sharing of its positive charge with the chelate rings.…”
Section: Antimicrobial Assaysmentioning
confidence: 99%
“…As our programme for the development of tetraazamacrocyclic complexes, we have recently reported [11][12][13][14][15] tin complexes of various macrocycles. Such studies have established [16] that [dicyclohexylcarbodiimide] (DCHC) and [4-dimethylaminopyridine] (DMAP) can act as good condensing reagents for the condensation of primary amine and dicarboxylic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the antibacterial activities of heavy rare earth complexes are stronger than those of the light rare earth complexes. The enhanced antibacterial activities of the complexes presumably result from the increase in liposolubility of the lanthanide complexes by the chelate effect …”
Section: Resultsmentioning
confidence: 99%
“…It is also evident that the complexes having sulfur as a donor atom in the ligand system display higher activity than those that do not have it. 39 6. Replacement of bismuth with antimony in its compounds reduced the compounds' antibacterial activities, 40,41 and we have also confirmed that antimony analogues of a compound have substantially lower levels of activity.…”
Section: Discussionmentioning
confidence: 99%